Emptiness and fullness : ethnographies of lack and desire in contemporary China - Bregnbæk, Susanne; Bunkenborg, Mikkel (Studies in social analysis ;, 2017)
As critical voices question the quality, authenticity, and value of people, goods, and words in post-Mao China, accusations of emptiness render things open to new investments of meaning, substance, and value. Exploring the production of lack and desire through fine-grained ethnography, this volume examines how diagnoses of emptiness operate in a range of very different domains in contemporary China: In the ostensibly meritocratic exam system and the rhetoric of officials, in underground churches, housing bubbles, and nationalist fantasies, in bodies possessed by spirits and evaluations of jade, there is a pervasive concern with states of lack and emptiness and the contributions suggest that this play of emptiness and fullness is crucial to ongoing constructions of quality, value, and subjectivity in China.